Experimental study on mechanical properties of steel tube-coupler connections in corroded scaffolds. (January 2021) - Hu, Xiaopeng; Peng, Gang; Niu, Ditao; Fan, Yongfeng
Abstract: The mechanical properties of steel tube-coupler connections significantly affect the bearing capacity and stability of steel tube-coupler scaffold systems; moreover, the corrosion of steel tubes and couplers will inevitably affect the mechanical properties of steel tube-coupler connections. The slipping and torsional tests were conducted on corroded right-angle coupler connections with five different corrosion ratios, and the mechanical properties of corroded steel tube-coupler connections were presented. The effects of corrosion degree on the slipping and torsional behaviors of right-angle coupler connections are discussed. The test results indicate that the shapes of the load ( P )–slipping ( Δ ) and torque ( T )–rotation ( θ ) curves of corroded right-angle coupler connections are similar to those of uncorroded steel tube-coupler connections. Moreover, with the increase in the corrosion ratio of the steel tube, both the slipping and torsional behaviors of the right-angle coupler connections improved. The slipping behavior presents a trend of escalation, whereas the torsional behavior shows a downward trend accompanied with an increasing corrosion ratio of the right-angle coupler. Based on the test results, empirical load ( P )–slipping ( Δ ) constitutive models and torque ( T )–rotation ( θ ) models of corroded right-angle coupler connections are proposed, by considering the corrosion ratio of the steel tube and coupler. Subsequently, the accuracy of the proposed models is verified by comparing the proposed models with test results from different sources. Graphical abstract: Unlabelled Image Highlights: Mechanical properties of corroded steel tube-coupler connections were tested. Effects of corrosions on properties of steel tube-coupler connections were discussed. Load-slipping models of corroded steel tube-coupler connections were proposed. Torque-rotation models of corroded steel tube-coupler connections were proposed. Agreement between proposed models and test data from different sources was achieved.